The Intelligence of Things: How AI Transforms the IoT Ecosystem - Самойдюк, Андрій; Остапчук, Оксана (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
This paper focuses on the integration of artificial intelligence (AI) into the Internet of Things (IoT) ecosystem and how this combination is transforming data-driven decision-making and system automation. The rapid growth of IoT devices has led to a huge amount of real-time data, creating new challenges for data processing, security, and system scalability. The goal is to analyze existing limitations and identify methods to improve IoT performance with AI-based solutions. The proposed approach focuses on intelligent data processing and adaptive learning models that improve automation, responsiveness, and predictive capabilities. Experimental studies show that AI-based IoT systems significantly outperform traditional IoT architectures in terms of data analysis and operational efficiency. Ця робота зосереджена на інтеграції штучного інтелекту (ШІ) в екосистему Інтернету речей (IoT) та на тому, як це поєднання трансформує автоматизацію систем та прийняття рішень на основі наявних даних. Швидке зростання популярності пристроїв IoT призвело до появи величезної кількості даних у режимі реального часу, створюючи нові виклики для обробки даних, безпеки та масштабованості систем. Метою є аналіз існуючих обмежень та визначення методів покращення продуктивності IoT за допомогою рішень на основі ШІ. Запропонований підхід зосереджений на інтелектуальній обробці даних та адаптивних моделях навчання, які покращують автоматизацію, швидкість реагування та прогностичні можливості. Експериментальні дослідження показують, що системи IoT на основі ШІ значно перевершують традиційні архітектури IoT з точки зору аналізу даних та операційної ефективності.